ALEXANDER AAN “ATHEIS MINANG” DI PROVINSI SUMATERA BARAT - Asnawati Asnawati (Harmoni, 2012)
The phenomenon of an emergence of writing in the virtual world which does not believe in the existence of God and religion or so-called “atheist” is a shock to the Minang people, because its author is a Minang citizen. It has been more controversial as it happens in the land of the Minang as “Minang Atheism”. This occurrence seems to hurt Minang people who have the philosophy of “Adat Basandi Syara’, Syara’ Basandi Kitabullah”. The problem becomes complicated because it uses the Qur’an and this study shows, it raises the disbelief in God and Islam. This study tries to describe the chronology of Aan arrest which occurred in January 2012 at the office of Bappeda Dharmasraya, because he made a writing on his Facebook account that essentially does not believe in God and religion. Aan did not broadcast the atheism on Facebook, but he merely became an administrator of the facebook with its name Minang Atheist. Being an administrator, he did not spread Atheism, but he made some comments on it. His Atheism has been part of his self since elementary school, after seeing the imbalance in the reality of life beset with sorrows and crimes associated with the understanding on his thoughts of God.